PENGARUH LINGKUNGAN KERJA, KONFLIK KERJA, DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN - I Made Astrama (Journal Social and Humaniora, 2017)
Increased competition, the impact on the role of consumers who are becoming increasingly important for the survival of most companies. Customers or consumers are now faced with various choices more than ever before. Therefore, the role of managed, it will determine the company’s success in the future. One factor is the key to organizational success is the role of the employee’s performance. Performance is the result of work that can be realized by employees of any work performed and serves as an assessment tool for the employee or the organization. So the employee’s performance will largely determine the performance of the organization. This research analyzes the causal relationship between variables, work environment, job satisfaction, and work conflict on employee performance in PT. Regional Development Bank Branch Karangasem Bali. The purpose of this study was to determine the e?ect of variable working environment, job satisfaction, and work conflict on employee performance in PT. Regional Development Bank Branch Karangasem Bali. This study examined the e?ect is causal because the independent variables (Work environment, job satisfaction, and conflicts of Work) to the dependent variable (Employee Performance). Object of research at PT. Regional Development Bank Branch Karangasem Bali diteli is 102 people, while the data were analyzed with statistical analysis tools Structural Equation Model (SEM) PLS. Based on the analysis it can be concluded that the work environment and job satisfaction and significant positive e?ect on employee performance, but variable labor conflict berpengaru terhadapa negative employee performance. Keywords: work environment, job satisfaction, work conflict, and employee performance.